Treatment stratification and prognosis assessment using circulating tumor DNA in locally advanced rectal cancer: A systematic review and meta‐analysis - Junjie Mi; Rong Wang; Xiaofang Han; Ruijun Ma; Danyu Zhao (Cancer Medicine, 2023)
Abstract Background Circulating tumor DNA (ctDNA) is an emerging biomarker for locally advanced rectal cancer (LARC), giving hope for stratified treatment. As the completed studies have small sample sizes and different experimental methods, systematic review and meta‐analysis were performed to explore their role in predicting pathological complete response (pCR), tumor recurrence, and prognosis. Methods PubMed, Embase, and the Web of Science were searched for potentially eligible studies published up to September 6, 2022. Pooled relative risk (RR) was calculated to predict pCR and tumor recurrence, and pooled hazard ratio (HR) was calculated to evaluate the prognosis of overall survival (OS), recurrence‐free survival (RFS), and metastasis‐free survival (MRS). Results Twelve studies published between 2018 and 2022 included 931 patients, and 2544 serum samples were eventually included in the meta‐analysis. The pooled revealed that ctDNA‐negative patients were more likely to have a pCR (RR = 1.64, 95% confidence interval [CI]: 1.26–2.12). The pooled revealed that ctDNA‐positive patients were at high risk of recurrence (RR = 3.37, 95% CI: 2.34–4.85) and had a poorer prognosis for OS (HR = 3.03, 95% CI: 1.86–4.95), RFS (HR = 7.08, 95% CI: 4.12–12.14), and MRS (HR = 2.77, 95% CI: 2.01–3.83). Conclusion ctDNA may be useful for stratifying treatment and assessing prognosis in patients with LARC, but its clinical application still needs to be confirmed in a prospective multicenter study with large samples.